Balancing the Pedagogical and Practical Concerns in Remote Higher Education: A Cyberethnography - Trinidad, Jose Eos R (Archīum Ateneo, 2021)
The COVID-19 pandemic brought about physical school closures and quick transitions online, with universities making decisions for this new mode of instruction. Such decisions, however, were open to discussion and debates, particularly as students and instructors held varying concerns, experiences, and expectations for remote learning. We investigate what these debates are using a cyberethnography of a Facebook group for students and faculty, and an anonymous Freedom Wall page for students in the same university. The concerns centered on workload that balanced academic rigor and practical exigencies; learning modalities that balanced accountability and flexibility; and assessments that balanced academic integrity and viable accommodations. Taken altogether, these suggest that faculty and students’ concerns are not merely about discrete curricular choices but are, at their root, about balancing pedagogical excellence and practical adaptability. We thus suggest that universities couch their policies not through discrete options but through the balancing of values.